Local culture and management styles of mampreneurs in Côte d’Ivoire: a quantitative study - KOBRI , Macoura Madina; LEDJOU , Djamanfoh Prisca-Nicaise (Revue Internationale du Chercheur, 2025)
Abstract Mumpreneurs, these women who combine entrepreneurship and motherhood, faced a double challenge: managing a business while meeting the sociocultural expectations linked to their role as mothers. In an Ivorian context where traditional values give a central place to the family and where the distribution of gender roles remains strongly anchored, these entrepreneurs develop a unique management style, influenced both by their maternal experience and Ivorian cultural norms. This reflection aims to better understand the logic of adjustment, the strategies adopted by mumpreneurs to assert their leadership, and the possible limits imposed or induced by culture on their managerial practices. To this end, a series of questionnaires was administered to a sample of 195 mothers and businesswomen operating in all sectors of the Ivorian economy. The results from the quantitative analysis using Jamovi 2.6.26 software show that cultural norms as well as gender positively influence the collaborative management style of mumpreneurs. Such an analysis would contribute to the recognition of the specificities of female management in highly cultural contexts and to propose support avenues adapted to this entrepreneurial profile.